Background concentrations of polycyclic aromatic hydrocarbons (PAHs) in deep core sediments from the Norwegian Sea and the Barents Sea: A proposed update of the OSPAR Commission background values for these sea areas. (July 2020) - Boitsov, Stepan; Klungsøyr, Jarle; Jensen, Henning K.B.
Abstract: Geochemical studies of 174 sediment cores collected by the MAREANO mapping program in Norwegian waters of the North Atlantic Ocean give new sets of values of background concentrations (BCs) for polycyclic aromatic hydrocarbons (PAHs) for the studied regions. The study is based on deep core sediment samples representing background levels of PAHs. The samples selected were only from the deeper parts of undisturbed sediment cores with low, stable concentrations of petrogenic and pyrogenic PAHs, with low variation for individual PAH compounds between the samples within the same core, and from below the parts of the cores dated with 210 Pb to approximately the last 100–150 years. The results show that the main part of the studied area has BCs different from those previously established by OSPAR Commission (OSPAR) for the North-East Atlantic. Another area in central Barents Sea has a separate set of BCs of pyrogenic PAHs, apparently due to the influence from marginal ice zone mechanisms. A third area with its own set of BCs has been established for north-western Barents Sea off the coast of Svalbard, due to high natural contents of PAHs in this area. BCs for several PAHs not included in the present OSPAR list are also provided. Highlights: PAHs in 174 cores from the eastern Norwegian Sea and the Barents Sea were measured. Background concentrations (BCs) of 25 PAHs were determined based on deep core data. The BCs are different from those established by OSPAR for the North-East Atlantic. Central Barents Sea (marginal ice zone) has its own set of BCs of pyrogenic PAHs. North-Western Barents Sea (Svalbard area) has its own, naturally high BCs of PAHs.